The Pembuatan Pupuk Organik Padat dari Limbah Pertanian dan Peternakan di Desa Batu Belah Kabuputen Kampar - Sunarno, Sunarno; Yenti, Silvia Reni; Fadli, Ahmad; Wisrayetti, Wisrayetti; Amri, Amun; Zultiniar, Zultiniar; Alfarizi, Cory Dian; Azis, Yelmida (Journal of Community Engagement Research for Sustainability, 2023)
Batu Belah Village is one of the villages located in the Air Tiris sub-district, Kampar Regency, with residents who mostly have a livelihood in agriculture. To increase the fertility of agricultural soil, fertilizer is needed. So far, the fertilizer commonly used is chemical fertilizer, but the price is relatively expensive, especially during the growing season, so it is necessary to find a solution to replace this chemical fertilizer. Organic solid fertilizer is a fertilizer that is friendly to the environment. This fertilizer can be made from agricultural and livestock waste, so it is very suitable to be developed in Batu Belah Village. The purpose of this activity is to provide knowledge and skills of the community in the technology of making organic solid fertilizer from agricultural and livestock waste. This service activity consists of two stages, namely a presentation on fertilizer manufacturing technology and the practice of making solid organic fertilizer with the farming community of Batu Belah village. The benefit of this activity is that the farming community can make their own organic solid fertilizer from agricultural and livestock waste, so that the cost of fertilizing on agricultural land can be reduced. Thus the income of the farming community can increase.